Interactions between ALKBH5 and reader proteins in tumors: functions and molecular mechanisms - Ou, Jiahui; Liu, Bingchen; Yu, Yi; He, Yingchun; Gao, Yuyu; Chen, Lingli; Chen, Xia; Tao, Huai (Frontiers in Oncology, 2025)
RNA methylation modifications are widespread in eukaryotes and prokaryotes, with N6-methyladenosine (m6A) methylation being the most prevalent internal modification in eukaryotic mRNA and having become a prominent focus of tumor research in recent years. Up to now, substantial evidence has suggested that the dysregulated RNA demethylase ALKBH5 can interact with m6A reader proteins to modulate a wide range of mRNA biological progress, including mRNA shearing, export, metabolism, and stability, ultimately influencing tumorigenesis and development. To deeply understand the regulatory roles of ALKBH5 and reader proteins in tumor progression, this review aims to summarize the structures of ALKBH5 and reader proteins, as well as their cooperative regulatory mechanisms that affect the occurrence and development of tumors originating from different systems. Furthermore, the potential applications of targeting ALKBH5 and reader proteins in antitumor drug development are summarized, hoping to provide a strong basis for advancing antineoplastic research in the future.